2015
DOI: 10.1140/epja/i2015-15137-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pion production data measured by HADES in proton-proton collisions at 1.25 GeV

Abstract: Baryon resonance production in proton-proton collisions at a kinetic beam energy of 1.25 GeV is investigated. The multi-differential data were measured by the HADES Collaboration. Exclusive channels with one pion in the final state (npπ + and ppπ 0) were put to extended studies based on various observables in the framework of a one-pion exchange model and with solutions obtained within the framework of a partial wave analysis (PWA) of the Bonn-Gatchina group. The results of the PWA confirm the dominant contrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 49 publications
(66 reference statements)
3
40
0
Order By: Relevance
“…The Beam Energy Scan (BES) program of RHIC [10] is currently investigating the location of the critical point [11]. The HADES experiment at GSI, Darmstadt is investigating a medium with very large baryon chemical potential [12]. In future, the Compressed Baryonic Matter (CBM) experiment [13] at the Facility for Antiproton and Ion Research (FAIR) at GSI and the Nuclotron-based Ion Collider fAcility (NICA) [14] at JINR, Dubna will also study nuclear matter at large baryon chemical potential.…”
Section: Introductionmentioning
confidence: 99%
“…The Beam Energy Scan (BES) program of RHIC [10] is currently investigating the location of the critical point [11]. The HADES experiment at GSI, Darmstadt is investigating a medium with very large baryon chemical potential [12]. In future, the Compressed Baryonic Matter (CBM) experiment [13] at the Facility for Antiproton and Ion Research (FAIR) at GSI and the Nuclotron-based Ion Collider fAcility (NICA) [14] at JINR, Dubna will also study nuclear matter at large baryon chemical potential.…”
Section: Introductionmentioning
confidence: 99%
“…This result was obtained using the hyperon production cross sections reduced by a factor of 0.75, as described in the previous Section. The Λ + Σ 0 multiplicity is still above (though within the error of) the experimental value of 0.017±0.003 obtained by HADES [28]. The squared matrix element of Y * production has been chosen to reproduce the experimental Ξ − yield of 2.0 × 10 −4 obtained by the HADES collaboration in p+Nb collisions.…”
Section: Resultsmentioning
confidence: 89%
“…The HADES collaboration has measured the yield of the doubly strange Ξ − baryon in p+Nb collisions at the subthreshold energy of √ s NN = 3.2 GeV [1], and in Ar+KCl collisions at the deeply subthreshold energy of √ s NN = 2.61 GeV [2]. They also performed a statistical model analysis of the obtained Ξ − yields along with their results for π, η, Λ, kaon, ω and φ multiplicities in the same reactions [3]. They found that the THERMUS statistical model gives a good description of all particle yields except for that of the Ξ − baryon, which the model underestimates by a factor 15 in the case of the reaction Ar+KCl and by a factor 8 in the case of the reaction p+Nb.…”
Section: Introductionmentioning
confidence: 99%
“…The Beam Energy Scan (BES) program of RHIC [10] is currently investigating the matter at large baryon chemical potential and the location of the critical point [11]. The HADES experiment at GSI, Darmstadt is also investigating a medium with very large baryon chemical potential [12]. In future, the Compressed Baryonic Matter (CBM) experiment [13] at the Facility for Antiproton and Ion Research (FAIR) at GSI and the Nuclotron-based Ion Collider fAcility (NICA) [14] at JINR, Dubna will study nuclear matter at large baryon chemical potential.…”
Section: Introductionmentioning
confidence: 99%